Factors affecting cloud ERP adoption in Saudi Arabia: An empirical study. (January 2019) - AlBar, Adnan Mustafa; Hoque, Md. Rakibul
Cloud ERP (Enterprise Resource Planning) systems have represented a paradigm shift in the information systems domain. They can provide flexibility, cost efficiency, scalability, adaptability, availability and configurable data to any type of company. This system has enjoyed rapid growth around the world. However, the adoption of cloud ERP in developing Middle Eastern countries such as Saudi Arabia is still in its infancy, and little research has been done to investigate this issue. This study examined the factors that influence the adoption of cloud ERP in the Kingdom of Saudi Arabia by combining the Diffusion of Innovation theory (DOI) and Technology-Organization-Environment (TOE) framework. The study found that a competitive environment, complexity, ICT infrastructure, observability, relative advantage, regulatory environment, ICT skill and top management support had a significant influence ( p < 0.05) on the adoption of cloud ERP, while compatibility, organizational culture and trialability had no significant ( p > 0.05) impact. The findings of this study will offer practical guidelines to the successful adoption of cloud ERP in Saudi Arabia and assist other developing countries in similar circumstances in planning and up-taking cloud ERP services.